2008
DOI: 10.4161/cbt.7.7.6172
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable enhancement of cytotoxicity of onconase and cepharanthine when used in combination on various tumor cell lines

Abstract: Onconase (Onc), a ribonuclease from oocytes or early embryos of Northern Leopard frog (Rana pipiens), is cytostatic and cytotoxic to a variety of tumor lines in vitro, inhibits growth of tumors in animal in vivo models and is currently in Phase IIIb clinical trials for malignant mesothelioma where it displays antitumor activity with minor overall toxicity to the patient. One of the characteristic features of Onc is a synergism with a variety of other antitumor modalities. Cepharanthine (Cep), a biscoclaurine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 57 publications
1
30
0
2
Order By: Relevance
“…In the present study, we further demonstrated that RC-6 also exerted anticancer effects on human embryonal carcinoma cells (NT2 cells). The results suggested that RC-6 may exert anticancer effects on various types of cancer, such as the RC-RNase-and onconase-exerted anticancer effects (21,(26)(27)(28)(29)(30)(31). Although the mechanisms of RC-6-induced cell cytotoxicity on cervical cancer cells has not been studied (29), RC-6-induced cell cytotoxicity in HepG2 cells was related to caspase-9/-3 cascade (45).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, we further demonstrated that RC-6 also exerted anticancer effects on human embryonal carcinoma cells (NT2 cells). The results suggested that RC-6 may exert anticancer effects on various types of cancer, such as the RC-RNase-and onconase-exerted anticancer effects (21,(26)(27)(28)(29)(30)(31). Although the mechanisms of RC-6-induced cell cytotoxicity on cervical cancer cells has not been studied (29), RC-6-induced cell cytotoxicity in HepG2 cells was related to caspase-9/-3 cascade (45).…”
Section: Discussionmentioning
confidence: 98%
“…Similar to RC-RNase, RC-6 (Rana catesbeiana ribonuclease-6) is also a frog ribonuclease derived from Rana catesbeiana (29,45). Previous studies demonstrated that onconase and RC-RNase can induce cell death in various cancer cells (21,(26)(27)(28)(29)(30)(31). However, only few studies showed that RC-6 inhibited cell growth in cervical cancer and hepatoma cells (29,45).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, numerous studies have indicated that RC-RNase is able to trigger distinct cell death mechanisms in various tumor cell types (10,11,14,17). By contrast, previous studies have also revealed that Onconase can exert antitumor activities in numerous tumor cells, including cervical, breast, colon, pancreatic and prostate cancer cells (12,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 95%
“…Фермент также потенцирует действие фактора не-кроза опухолей и апоптоз опухолевых клеток. Среди опухолей кроветворной системы к ранпирназе ока-зались чувствительными клетки промиелоцитарного лейкоза RPMI-8228 [14]. Применение фермента не сопровождается гематологической, кардио-и гепа-тотоксичностью.…”
unclassified